CODE SWITCHING USED BY PUBLIC FIGURES IN DEDDY CORBUZIER'S PODCAST: SOCIOLINGUISTICS APPROACH - Rika Fiorensera; Nurma Dhona Handayani (Universitas Putera Batam, 2021)
Sociolinguistics is a joint scientific discipline between sociology and linguistics which means the relationship between society and language. In this case, sociolinguistics is the relationship and mutual influence between language behavior and social behavior. A language is an object of study of the social structures in society as means of communication and group identity. The ability of each human being in the language is different. Some people use two languages in their daily life which is called bilingual. most people like to switch languages with their interlocutors as needed. In sociolinguistics, there is code-switching which is related to bilingualism. Code-switching refers to a kind of code to switch between two languages of the same language at the same time. Code-switching here is a necessary ability to build in an ever-evolving multicultural environment. From social media, people can learn many languages ​​and explore various languages ​​used by others. Almost everyone uses social media. One famous artist who has a YouTube channel with many subscribers is Deddy Corbuzier. In Deddy Corbuzier's podcast, Deddy Corbuzier tends to switch Indonesian English with the other public figures. Therefore, this research aims to describe the types of code-switching using in Deddy Corbuzier podcast. There are three types such as tag switching, intersentential switching, and intrasentential switching. The data was analyzed by using Stockwell (2002) theory. The researchers used descriptive qualitative research methods to research by using (Sudaryanto, 2015). The results of this research, researchers found 3 data for tag switching, 1 data for intersentential switching, and 5 data for intrasentential switching.